Investments in fixed assets and depreciation of fixed assets: theoretical and practical aspects of study and analysis - Irina D. Demina; Elena I. Larionova; Tatiana I. Chinaeva (Статистика и экономика, 2017)
It is indicated that domestic economy is experiencing a shortage of investment.The acceleration of the processes of import substitution is one of the most important challenges facing the domestic economy at present.Investments, especially capital investments and related investment relations constitute the basis for the development of the national economy and improving the efficiency of social production as a whole. A problem of formation of the amortization fundremains actual at the moment. In the modern scientific and educational literature amortization fund means the fund, including the use of funds to complete the restoration and repair of the fixed assets. This paper makesthe analysis of the situation in the area of investment in the fixed capital, which has developed in Russia for the past severalyears. The aim of this paper is to study the investment climate in the country based on the analysis of investments in the fixed capital by the sources of financing and types of the economic activity. The work is based on dynamic and structural analysis of analytical and statistical information on the processes occurring in this field.As a result, it can be noted that in spite of a number of efforts being made, in general, there are low growth rates in industry, there is a deficit of investments in the fixed assets. Most of the investments in fixed assets are carried out at the expense of the organizations’ own funds. A significant number of economic entities do not have the means, necessary for the technological renewal. Unfortunately, the regulatory framework in the field of accounting for the fixed assets and accrual of depreciation does not imply the use of a special account for the accumulation, and, most importantly, for the purposeful control of the use of the depreciation fund.First of all, it is necessary for companies with state participation and monopoly organizations. The lack of control over the targeted use of the depreciation fund led to a deterioration in the dynamics of indexes, characterizing the state and movement of the fixed assets, as evidenced by data on relevant indexes. Accelerated depreciation, used in tax accounting, should be monitored. However, at present, this only leads to an increase in costs. The article proposes accounting entries for the formation of an amortization fund and information on its intended use. In IFRS standards, information on the amount of accrued depreciation on fixed assets is generated in the reporting, which should also be shown in the financial statements of domestic organizations (especially with the state participation). Ambiguity in the interpretation of legislative and regulatory acts in the field of accounting for the fixed assets, accrual of depreciation and the formation of an amortization fund does not contribute to improving the investment climate in the country and leads to significant wear and tear in virtually all sectors of the economy. The article concludes that there is a significant underinvestment of the domestic economy, especially for manufacturing organizations.